2016
DOI: 10.3847/0004-637x/832/2/151
|View full text |Cite
|
Sign up to set email alerts
|

ALMA REVEALS WEAK [N ii] EMISSION IN “TYPICAL” GALAXIES AND INTENSE STARBURSTS AT z = 5–6

Abstract: We report interferometric measurements of [Nii] 205 µm fine-structure line emission from a representative sample of three galaxies at z = 5-6 using the Atacama Large (sub)Millimeter Array (ALMA). These galaxies were previously detected in [Cii] and far-infrared continuum emission and span almost two orders of magnitude in star formation rate (SFR). Our results show at least two different regimes of ionized inter-stellar medium properties for galaxies in the first billion years of cosmic time, separated by th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
132
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(144 citation statements)
references
References 86 publications
(120 reference statements)
12
132
0
Order By: Relevance
“…However, IGM absorption and outflows cannot account for velocity shifts relative to other UV transitions (e.g. CIII or UV absorption features, as in the case of Capak et al 2015) and obviously cannot account for velocity shifts between different far-IR transitions, as observed by us and others (Pavesi et al 2016;Decarli et al 2014). In fact, all far-IR and UV emission lines, whose emission is not absorbed by IGM, should have the same velocity offsets if they are emitted from the same region of the galaxy.…”
Section: Spatial and Spectral Offsetsmentioning
confidence: 75%
“…However, IGM absorption and outflows cannot account for velocity shifts relative to other UV transitions (e.g. CIII or UV absorption features, as in the case of Capak et al 2015) and obviously cannot account for velocity shifts between different far-IR transitions, as observed by us and others (Pavesi et al 2016;Decarli et al 2014). In fact, all far-IR and UV emission lines, whose emission is not absorbed by IGM, should have the same velocity offsets if they are emitted from the same region of the galaxy.…”
Section: Spatial and Spectral Offsetsmentioning
confidence: 75%
“…The ratio of LAB1-ALMA3 is shown, compared with those of various galaxies at z∼5 (Decarli et al 2014;Rawle et al 2014;Béthermin et al 2016;Pavesi et al 2016 and references therein) and local (U)LIRGs (Díaz-Santos et al 2013;Zhao et al 2016). ALMA3 shows one of the highest values seen to date, which indicates an enhanced [C II] emission.…”
Section: Discussion and Summarymentioning
confidence: 97%
“…In particular, it is used to evaluate global trend on the fraction of [C II] emission associated with ionized regions (i.e., HII regions; e.g., Oberst et al 2006;Decarli et al 2014;Pavesi et al 2016), mainly because nitrogen's ionization potential (14.5 eV) is higher than that of hydrogen (13.6 eV) so that [N II] arises only from ionized regions. Pavesi et al (2016) reported the expected a line ratio…”
Section: Discussion and Summarymentioning
confidence: 99%
See 2 more Smart Citations